Characterizing the epithelial–mesenchymal transition status of circulating tumor cells in head and neck squamous cell carcinoma. Issue 11 (5th August 2022) - Payne, Karl; Brooks, Jill; Batis, Nikolaos; Taylor, Graham; Nankivell, Paul; Mehanna, Hisham
Abstract: Background: Circulating tumor cells (CTCs), in particular those undergoing an epithelial–mesenchymal transition (EMT), are a promising source of biomarkers in head and neck squamous cell carcinoma (HNSCC). Our aim was to validate a protocol using microfluidic enrichment (Parsortix platform) with flow‐cytometry CTC characterization. Method: Blood samples from 20 treatment naïve HNSCC patients underwent Parsortix enrichment and flow cytometry analysis to quantify CTCs and identify epithelial or EMT subgroups—correlated to clinical outcomes and EMT gene‐expression in tumor tissue. Results: CTCs were detected in 65% of patients (mean count 4 CTCs/ml). CTCs correlated with advanced disease ( p  = 0.0121), but not T or N classification. Epithelial or EMT CTCs did not correlate with progression‐free or overall survival. Tumor mesenchymal gene‐expression did not correlate with CTC EMT expression ( p  = 0.347). Discussion: Microfluidic enrichment and flow cytometry successfully characterizes EMT CTCs in HNSCC. The lack of association between tumor and CTC EMT profile suggests CTCs may undergo an adaptive EMT in response to stimuli within the circulation.